2017
DOI: 10.1007/s00384-017-2805-9
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers as early predictors of infection after colorectal surgery: the same cut-off values in laparoscopy and laparotomy?

Abstract: The impact of infection on inflammatory markers is more important than that of the surgical approach. Defining a specific cutoff value for early discharge according to the surgical approach is not justified. A patient with CRP values lower than 100 mg/L on POD 4 can be safely discharged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 34 publications
1
21
1
1
Order By: Relevance
“…The CRP test is commonly used to indicate the presence of inflammation in many diseases. Many studies have confirmed its sensitivity in demonstrating inflammation after surgery [26–28]. Until now, there is no solid evidence to support its use before surgery, and none of the previous studies investigated its role in urolithiasis diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The CRP test is commonly used to indicate the presence of inflammation in many diseases. Many studies have confirmed its sensitivity in demonstrating inflammation after surgery [26–28]. Until now, there is no solid evidence to support its use before surgery, and none of the previous studies investigated its role in urolithiasis diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, these outcomes were often rated poorly for validity and reliability by both the wider study group (in round 2) and the theme subgroup (in round 3). Although clinical teams continue to use these inflammatory markers, particularly CRP, to guide antibiotic therapy, 19,20 there is little evidence to ▪ Infection involves a part of the body deeper than the fascial/muscle layers, that is opened or manipulated during the operative procedure AND one of [purulent drainage from drain in organ/space OR organisms identified from aseptically obtained fluid or tissue in the organ space by a culture or non-culture based testing method which is performed for the purposes of clinical diagnosis and treatment OR an abscess or other evidence of infection involving the organ/space that is detected on gross histopathologic examination OR imaging test evidence suggestive of infection] ▪ Within 30 days y Sepsis z ▪ Increase in SOFA score of 2 or more, with evidence of infection ▪ Within 30 days y Septic Shock z ▪ Sepsis (SOFA score or 2 or more with evidence of infection) with shock ▪ Vasopressor requirement to maintain a mean arterial pressure of 65 mm Hg or greater and serum lactate level greater than 2 mM (>18 mg dl À1 ) in the absence of hypovolaemia suggest they reliably differentiate inflammation from infection. 21e24…”
Section: General Markers Of Infection and Inflammationmentioning
confidence: 99%
“…The release of in ammatory factors is associated with postoperative complications including increased risk of postoperative infections (4)(5)(6)(7). In turn, sepsis is associated with increased rates of postoperative mortality, prolonged hospital stay, and increased health care costs (8).…”
Section: Introductionmentioning
confidence: 99%
“…Heparin-binding protein, also known as CAP37 or azurocidin, is a multifunctional, inactive serine-protease homologue (10). It is stored in azurophilic granules and secretory vesicles of neutrophils and released upon stimulation, and is able to recruit and activate monocytes, mobilize T cells and to induce detachment and homotypic aggregation of the endothelial cells (7,11). Furthermore, HBP has been shown to play a key role in inducing vascular leakage by mediating increased capillary permeability (12).…”
Section: Introductionmentioning
confidence: 99%